Object oriented toolkits for simulation program generators - Ulgen, O. M.; Thomasma, T.; Mao, Y. (Proceedings of the 21st conference on Winter simulation, 1989)
Simulation Program Generators (SPGs) developed using object-oriented environments may be designed to have a number of capabilities not available in traditional SPGs. One such capability is the description of an object's behavior from scratch without any programming when such behavior does not exist in the knowledgebase of the SPG. SmarterSim is an SPG that is currently being developed to provide the user a number of object-oriented tools including libraries of elemental operations, actions/requests, states, and rules and a number of function block templates to create new behavior using the existing primitive elements. The behavior of objects in a robotic manufacturing cell is described using SmarterSim. Like its predecessor SmartSim, SmarterSim supports a hierarchical, modular modeling for building of subsystems (coupled models) from model objects (atomic models) using subsystem management features. The paper also discusses the use of object oriented environments for traditional SPGs and simulation programming languages.